A Strategy for Assessing Continuity in Terrestrial and Maritime Landscapes from Murujuga (Dampier Archipelago), North West Shelf, Australia. (1st October 2020) - Veth, Peter; McDonald, Jo; Ward, Ingrid; O'Leary, Michael; Beckett, Emma; Benjamin, Jonathan; Ulm, Sean; Hacker, Jorg; Ross, Peter J.; Bailey, Geoff
Abstract: Over the last 20, 000 years, one third of the continental land mass of Australia, or 2.12 million km 2, has been drowned by postglacial sea-level rise. Much of this drowned territory is thought to have been occupied by humans. Where archaeological remains have survived inundation, they can be investigated by underwater and airborne remote sensing, survey, and ground-truthing. This study of the Dampier Archipelago of North West Australia is contextualized by a review of the current state of the art of underwater prehistory. In the absence of known sites, we propose terrestrial analogy as a predictive tool for targeting submerged archaeological sites. Geological and topographic contexts are important for assessing preservation potential as is identifying landforms and features around which people may have focused occupation. Analysis of more than 2, 500 known archaeological sites from the extraordinarily rich Dampier Archipelago reveals that the vast majority are rock art sites, but these are interspersed by a significant number of artifact scatters, myriad stone structures, shell middens, and quarry and reduction areas. The majority of these sites are focused on coastal and interior valleys, associated uplands, and coastal embayments. While over two thirds of sites occur on granophyre and basalt substrates, the others are located on Quaternary sediments. Regional research on nearby continental islands shows that use of these environments can be expected to pre-date sea-level rise. The most likely submerged sites include: 1) compacted middens associated with rock pools and estuarine features; 2) stone structures with associated middens on limestone pavements or with granophyre and basalt boulder fields; 3) buried midden and other occupation deposits on protected sand sheets; 4) quarry outcrops, extraction pits, and associated reduction debris in areas of fine-grained granophyre and basalt; and 5) middens in consolidated calcarenite shoreline contexts to the north and west of the volcanic suites of the Dampier Archipelago.